The Effect of Using The Virtual Laboratory on The Achievement of First-Year Middle School Students In Science” (Journal of the College of Basic Education, 2025)
The aim of the current research is to find out (The effect of using the virtual laboratory on the achievement of first-year middle school students in science). The researchers used the experimental design with partial control in two equal experimental and control groups, and according to this design, the research sample was intentionally selected from the research community, which represented (intermediate and secondary government day schools in the center of Karbala Governorate affiliated to the General Directorate of Education of Karbala) and it was (the second high school for girls) , The researchers rewarded the two groups in the following variables: chronological age calculated in months, intelligence, testing previous information, and the scientific material was identified, consisting of three units, which are: (the first unit: matter, the second unit: the periodic table, the third unit: strength and energy from the science book for the first intermediate grade, 5th edition, 1441 AH / 2021 AD). The researchers conducted a field experiment that lasted a full semester, as the experiment was implemented in the first semester of the academic year (2022-2023) for approximately (10) weeks and three classes per week for each of the experimental and control groups. The behavioral objectives of these chapters were formulated, as the final number reached (80) behavioral objectives. With regard to the research tool, the researchers built the research tool, which was an achievement test in science, consisting of (30) objective items of multiple choice type with four alternatives. After applying the research tool and analyzing the results, the researchers reached the statistical results using (Microsoft Excel) and the (SPSS) system. The psychometric properties of the scale were confirmed, which were its validity, reliability, discrimination and difficulty coefficients. The results showed that the students of the experimental group who studied the science subject according to the virtual laboratories were superior to the students of the control group who studied the same subject according to the usual method in the achievement test .Therefore, the researchers recommended the necessity of introducing teaching staff to training courses on how to use interactive simulation programs, including (virtual laboratories) and smart screens, to develop their scientific and practical capabilities, in addition to encouraging and motivating them to use them. They also suggested conducting research on the effect of the virtual laboratory on other dependent variables such as (technological awareness, technological culture, inclination, scientific thinking skills).